2013
DOI: 10.1155/2013/419212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acupuncture on Heart Rate Variability in Beagles; Preliminary Results

Abstract: Evidence-based animal experimental research concerning the effects of acupuncture on autonomic function was performed by two research teams from China and Austria. This study describes measurements in beagles. Heart rate variability (HRV) recordings were performed under stable conditions in Beijing, China, and the data analysis and interpretation were completed in Graz, Austria. The electrocardiograms were recorded during bilateral body acupuncture (PC6, Neiguan). Power of the low frequency (LF), high frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…HRV as an indicator for the bidirectional relationship between autonomic activation and different pain conditions has also been studied in horses (Rietmann et al, 2004), calves (Stewart et al, 2010), and sheep (Stubsjøen et al, 2009). Research on canine autonomic function in relationship to different pathologic conditions (Pirintr et al, 2012;Rasmussen et al, 2012) and assessments on canine cardiac modulation during physical intervention is a matter of great interest because of the potential value as an outcome measure (Wang et al, 2013). As changes in cardiac activity are influenced by psychological and emotional states in dogs (Kuhne et al, 2014a) there are potential clinical applications for short-term HRV parameters as outcome measures for the relief of pain and stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HRV as an indicator for the bidirectional relationship between autonomic activation and different pain conditions has also been studied in horses (Rietmann et al, 2004), calves (Stewart et al, 2010), and sheep (Stubsjøen et al, 2009). Research on canine autonomic function in relationship to different pathologic conditions (Pirintr et al, 2012;Rasmussen et al, 2012) and assessments on canine cardiac modulation during physical intervention is a matter of great interest because of the potential value as an outcome measure (Wang et al, 2013). As changes in cardiac activity are influenced by psychological and emotional states in dogs (Kuhne et al, 2014a) there are potential clinical applications for short-term HRV parameters as outcome measures for the relief of pain and stress.…”
Section: Introductionmentioning
confidence: 99%
“…As changes in cardiac activity are influenced by psychological and emotional states in dogs (Kuhne et al, 2014a) there are potential clinical applications for short-term HRV parameters as outcome measures for the relief of pain and stress. This concept has been used to study various interventions and exercise regimens for possible effects on the autonomic nervous system in humans (Haker et al, 2000;Anderson et al, 2012;Takamoto et al, 2009;Figueroa et al, 2008;Farinatti et al, 2011;Janse van Rensburg et al, 2012) and in dogs, but to a lesser extent (Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, inflammation response is one of the common causes for postoperative pain. Studies showed that electrical stimulation of LI4 and PC6 acupoints inhibits sympathetic activation, enhances vagal activity, helps to maintain the hemodynamic stability, and reduces the stress response in vivo [ 23 , 24 ]. Therefore, BL23, SP9, LI4, and PC6 were selected as the target acupoints in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Qigong is known as an easily adaptable form of gentle mind-body exercise that can be practiced at any place and time without any special equipment, and it is a widely used self-care CAM method in promoting physical and mental well-being (Jahnke, Larkey, Rogers, Etnier, & Lin, 2010). Studies have shown that qigong training reduces stress and anxiety (Wang, Litscher, Shi, Jiang, & Wang, 2013).…”
Section: Introductionmentioning
confidence: 99%